A mixed methods investigation of an online intervention to facilitate student midwives' engagement in effective conversations about weight-related behaviour change with pregnant women. (August 2018) - Hart, Jo; Furber, Christine; Chisholm, Anna; Aspinall, Samantha; Lucas, Charlotte; Runswick, Emma; Mann, Karen; Peters, Sarah
Highlights: Training for student midwives increases behaviour change knowledge, and confidence/beliefs to have healthy conversations. Training didn't change intentions/attitudes for healthy conversations, but pre training levels were already high. Online training for student midwives is feasible/acceptable. They felt prepared having these conversations in practice. Abstract: Objective: (1) To identify whether an online training intervention could increase midwifery students' knowledge of behaviour change techniques (BCTs) and intentions to use them in practice. (2) To identify students' views and current experiences of talking to women about weight-related behaviour change. Design: Mixed methods study involving pre- and post-training assessments, and qualitative interviews with midwifery students. Setting: Online training course delivered at a University in the North of England, UK. Participants: Midwifery students in the third year of their undergraduate degree during 2015–2016. Intervention: Online training focused on equipping students with knowledge of theoretically-informed BCTs, and the skills to use them opportunistically in existing practice settings. Measurements: Likelihood of discussing obesity with women was assessed via a 12-item, 7-point Likert scale assessing students' attitudes, subjective norms, perceived behavioural control, and intentions. A 14-item checklist was used to assess BCT knowledge whereby students selected recognised BCTs (of 7 correct, 7 false). Students' views and experiences of current practice was explored through in-depth, semi-structured one-on-one interviews with a member of the research team. Findings: Students' subjective norms, perceived behavioural control, and knowledge of BCTs increased post-training but intention and attitudes did not. Interviews revealed three themes accounting for students experiences and views of behaviour change practice: (1) 'How training fits with current encounters with maternal obesity in midwifery training' (2) 'TEnT PEGS prepares students for practice', and (3) 'Value of tailored training'. Key conclusions: Online BCT training can improve the midwifery students' confidence, knowledge and beliefs that this is part of their role. They also reported finding the training helpful in better preparing them for this challenging element of their routine practice. Implications for practice: Online BCT training can be used to prepare undergraduate midwifery students for practice.